‘He has a life a soul a meaning that extends far deeper than his medical assessment … ’: The role of reflective diaries in enhancing reflective practice during a rural community physiotherapy placement - J Potterton; Hellen Myezwa; Douglas Maleka; Patricia McInerney; Briony Watt (South African Medical Association, 2017)
Background. The Department of Physiotherapy at the University of the Witwatersrand, Johannesburg, South Africa has a programme that allows 4th-year physiotherapy students to experience learning about public health in a rural setting. This experience is assessed using a portfolio. To date, the portfolios have only been assessed in terms of the students achieving the learning objectives. The process has not been evaluated for its effectiveness in promoting a reflective learner. A reflective learner is considered as one who will develop critical thinking and better accountability for their own learning.Objective. To analyse the level of reflective practice attained by the students.Methods. A qualitative approach was used to analyse evidence of reflective practice in student reflective diaries. Guided content analysis, using a framework compiled from the literature, was used to code the data. The coding framework outlined the levels of reflective practice â€" from the lowest level, identifying learning outcomes, to the highest level, i.e. abstract concept formation.Results. Forty-eight portfolios with reflective diaries were available for analysis. Data saturation was obtained after eight reflective diaries were analysed. The majority of the student diaries (6 of 8) reflected a low level of reflective practice, with only a few attaining a high level.Conclusion. This study showed that physiotherapy students who experienced learning in a rural setting achieved low levels of reflective practice. A minority of students were able to progress in their reflection to reveal elements of critical thought, reflective thinking and, further still, abstract concept formation.